OPTIMALISASI RUANG HIJAU: PEMBERDAYAAN MASYARAKAT MELALUI VERTICAL GARDEN - Rahmansyah, Ahmad Iskandar; Hudzafidah, Khusnik; Murni, Cahyasari Kartika; Bahri, Mohammad Saiful; Krisnawati, Titin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
This community service outlines the detailed process of identifying local potential and needs, as well as implementing education and community participation in the development of the Vertical Garden in the Dringu Village. The project team actively collaborates with village officials, community cadres, PKK, and school teachers through participatory discussions, consultations, and systematic surveys. This inclusive approach ensures that the Vertical Garden is tailored to the specific aspirations of the local community. The education phase involves interactive workshops, practical sessions, and strategic collaborations with schools to enhance the community's understanding and practical skills. The steps of routine monitoring and maintenance include the formation of a local monitoring team, regular inspections, and active community involvement in ongoing care. A transparent reporting system and periodic evaluations facilitate continuous adjustments. Overall, the Vertical Garden project in Dringu has successfully created green spaces and empowered the community through active participation and deeper environmental education.